(3ebGdI aj GdMhGS (B( (3hUhQgG hcjajI ehGbYgG hfSH HYVgG Edi HYV (B)s - (3YHO GddWja Hf jhSa Hf eMeO Hf Ydj GdHZOGOj, ehab GdOjf, hjYQa HGHf GddHGO, hHGHf fbWI,J (B629 (3g` s
(3ChdgG (B:s
(3GdMhGS GdNeS dcd hGMO efgG EOQGc heOQc NGU , hLejY Pdc jTJQc ajg GdMjhGf GdfGWb hGdCYLei , hEfeG jNJda HGdCbd hGdCcKQ hGdCbhi hGdCVYa s
(3BNQgG (B:s
(3hdG ffcQ Cf dfG ai GdMhGS hSGFQ GdCYVGA CUfGakG ef GdeYhbGJ ceG jfhH GdHUQ Yf GdSeY ai bQGAI GdecJhH , hGdjO Yf GddSGf ai GdcJGHI ,hCYVGA GdhLg hGdjO hGdQCS HGdETGQI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B5(3H (B- (3U(B7(3Cs
(3ZjQ GdebGdI GdSGHbI GfXQgG HYO GdebGdI GdSGHbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B61 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B15s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B246 s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdWHs